Analisis Konsentrasi Total Suspended Particulate (TSP) Udara Ambien Dan Proyeksi Risiko Kesehatan Di Kota Kupang - Sambur, Ma'aki M. D.; Suwari, Suwari N.; Nitti, Fidelis (Universitas Nusa Cendana, 2022)
This study aims to determine the concentration of Total Suspended Particulate (TSP) in Kupang City and analyze public health risks. The sampling method used is the High Volume Air Sampler (HVAS) according to SNI 7119-3-2017. XRF analysis was carried out to determine the elements in the particulates. The results of the analysis showed that the highest concentration of TSP was 175.768 μg/m3. The highest intake value is 0.0206 mg/kg/day, the highest RQ value is 0.008. The elements detected were Si, K, Ca, Ti, Fe, Ni, Cu, Zn, Sr, Ba, Ce, Eu, and Yb. The results of the analysis show the concentration of TSP based on PP RI quality standards No. 22 of 2021 is still within safe limits, so there is no risk to public health in Kupang City.